Icaritin alleviates motor impairment and osteoporosis in Parkinson’s disease mice via the ER-PI3K/Akt pathway - Xianmei Lin; Xinyu Zhou; Xingman Liu; Lingqiong Xia; Jing Cai; Nanqu Huang; Yong Luo; Weidong Wu (Scientific Reports)
Abstract This study investigates the role of flavonoid Icaritin (ICT) in estrogen-deficient ovariectomized (OVX) female mice by activating the Estrogen receptor (ER)/ Phosphatidylinositol 3-kinase (PI3K)/Protein kinase B (Akt) signaling pathway, potentially delaying Parkinson’s disease (PD) progression post-castration. Seventy-five 8-week-old C57BL/6J female mice underwent ovariectomy, followed by MPTP (20 mg/kg) injection for 7 days. ICT (20 mg/kg) was administered for 14 days, and motor function was assessed using various behavioral tests. Serum estradiol, FSH, LH levels were measured by ELISA, and the expression of PI3K/Akt signaling and apoptosis proteins was analyzed by Western blot. Bone mineral density was assessed via dual-energy X-ray absorption, and histology of the uterus and femur was performed. Results showed that ICT alleviated MPTP-induced motor deficits, increased serum estradiol, and improved uterine atrophy. At the molecular level, ICT activated the PI3K/Akt pathway, reduced apoptosis, and mitigated PD symptoms and osteoporosis induced by OVX. These findings suggest ICT may offer therapeutic potential in managing OVX-induced motor dysfunction and PD.